Does Lateral Internal Sphincterotomy Impact the Outcome of Haemorrhoidectomy - Ammarah Afzal, Kamran Zaib Khan, Gul-E-Lala, Mian Umar Javaid, Khushbakht Ali Khan, Laiq Folad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The most common complication after hemorrhoidectomy is almost always postoperative. This dreadful complication makes the patients postpone the treatment even for prolapsing, bleeding, and uncomfortable piles. There are different methods that can be used for reducing pain including performing a lateral internal sphincterotomy (LIS). Better outcome of hemorrhoidectomy combined with lateral internal sphincterotomy has been observed in a few past controlled trials with respect to decreased pain after surgery, and improved and early wound healing. Objective: To compare the mean post-operative pain score in patients undergoing open hemorrhoidectomy with and without lateral internal sphincterotomy for III and IV degree hemorrhoids. Study Design: Randomized control trial. Place and Duration of Study: Department of Surgery, Jinnah Hospital Lahore from 1st July 2021 to 31st December 2021. Methodology: One hundred and twenty patients with diagnosis of III & IV degree hemorrhoids were selected. They were divided in two groups, Group A included patients who underwent open hemorrhoidectomy with lateral sphincterotomy and Group B included patients who underwent open hemorrhoidectomy alone. Standard Milligan Morgan Hemorrhoidectomy was done under local anesthesia. A fine surgical blade was inserted in inter-sphincteric groove with blade parallel to the circular fibers of internal sphincter. Blade was then rotated so that it faces the lumen of the anal canal. With the surgeon’s index finger in the canal, the blade was advanced towards the index finger so as to divide the internal sphincter but not the anal mucosa. Post-operative pain was assessed at first 48 hours post operatively according to ‘Visual Analog Score’. Results: The mean age was 34.6±7.72 in Group A and 34.28±8.09 years in Group B. There were 34 (56.67%) males in Group A and 32 (53.33%) in Group B while 26 (43.33%) females in Group A and 28 (46.67%) in Group-B. The mean pain score was 1.43±0.49 in Group A and 2.03±0.74 in Group B (P=0.001). Conclusion: Open hemorrhoidectomy with lateral sphincterotomy results in significantly lower mean post-operative pain when compared to open hemorrhoidectomy alone Keywords: Hemorrhoids, Open hemorrhoidectomy, Lateral sphincterotomy, Post-operative pain